2003
DOI: 10.1007/s00423-003-0400-8
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral endostatin gene transfer inhibits growth of human lung cancer in a murine orthotopic xenotransplant model

Abstract: Retroviral transduction of the human endostatin gene is capable of achieving long-term endostatin expression. Endostatin transduction provides significant anti-tumor effects with regard to local tumor growth, metastases and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…These results are in line with experimental studies on other cancer subtypes in which endostatin suppresses tumor growth. [3][4][5]8,16,23,26,30,33,35,[37][38][39]48 In contrast to previous work, however, we did not observe significantly prolonged survival or tumor volume reduction after treatment with human endostatin. The reason for this discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 74%
“…These results are in line with experimental studies on other cancer subtypes in which endostatin suppresses tumor growth. [3][4][5]8,16,23,26,30,33,35,[37][38][39]48 In contrast to previous work, however, we did not observe significantly prolonged survival or tumor volume reduction after treatment with human endostatin. The reason for this discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 74%
“…However, as this fragment is thought to exert its antiangiogenic function by interacting with integrin a1b1 [27], it is an unlikely candidate for inhibition of tumor angiogenesis in the integrin a1-null mice. In addition to the collagen IV NC1 domains, it has been demonstrated that lung tumors derived from NSCLC cells engineered to secrete endostatin are smaller and less metastatic than tumors derived from control NSCLC cells [28]. Although endostatin can be generated from purified collagen XVIII by MMP7 [29] and a1-null endothelial cells produce more MMP7 than their wild type counterparts [6], we have not explored the contribution of this molecule in our mouse model.…”
Section: Orthotopic Model Of Nsclcmentioning
confidence: 96%
“…Different gene constructs have been used in different cancer model by intratumor injection [24], subcutaneous administration [25] or low voltage electroporation [26]. The endostatin gene was even retrovirally transduced to tumor cells and the transduced cells were subsequently xenotransplanted in a murine tumor model [27]. Kurosaka et al [28] reported that systemic administration of endostatin can inhibit pannus formation and bone destruction in arthritis.…”
Section: Introductionmentioning
confidence: 99%